La médiatisation des troubles liés à l’adolescence dans la presse quotidienne nationale française (1995-2009) - Audrey Arnoult (Communication)
This research brief presents the author’s PhD analysis of the media coverage of adolescent disorders. The coverage by five French dailies — La Croix, Le Monde, Le Figaro, Libération and L’Humanité — between 1995 and 2009 was selected. A quantitative and qualitative analysis of 989 articles was conducted. The aim was to understand how the press makes sense of social, medical and legal transgressions by adolescents suffering from psychological distress.